홍화 재배유형 및 수확시기가 종실 수량 및 품질에 미치는 영향 - 김재철; Jae Cheol Kim; 김기재; Ki Jae Kim; 최성용; Seong Yong Choi (Korean journal of crop science, 2005)
홍화의 노지및 하우스재배의 생육과 수량 및 수확시기별 종실의 품질에 대한 시험결과를 요약하면 다음과 같다. 하우스비가림재배가 노지재배에 비해 출현기는 3일, 개화기는 8일이 빨랐으며, 생육도 양호하여 10g당 종실수량도 노지재배 보다 25~% 증수되어 노지재배 보다 비가림재배가 유리하였다. 조지방함량은 비가림하우스재배가 노지재배보다 높았고 종자의 색택도 비가림하우스재배에서 변색없이 흰색이었으나 노지재배에서는 변색되어 품질이 나빴다. 노지재배의 조지방 함량은 수확기까지 높아졌으며 개화성기 20일 이후 수확에서는 차이가 없었으나, 종실의 색깔은 개화성기 30일 이후 점차 변하여 개화성기 후 40일 수확은 흑갈색으로 종실품질이 크게 떨어져 종실의 수확시기는 개화성기 후 20일에서 30일 사이가 가장 좋았다. This study was conducted to investigate the plant growth and seed yield between rain-shelter plastic house and out-door cultivation, and analysed the effect of harvesting time on seed quality. In rain-shelter plastic house cultivation, emergence date was 3 days and flowering date was 8 days earlier than out-door cultivation. Seed yield of rain-shelter plastic house cultivation was increased 25~% compared to out-door cultivation and it's more beneficial than out door cultivation. The crude fat content was higher and seed was whiter and better quality in rain-shelter plastic house cultivation than out-door cultivation. In out-door cultivation, the crude fat content was steadily increased until 40 days after full bloom, but the seed color was getting dark which was harvested at 30 days after full bloom and the color was turn to the dark brown when the seed was harvested at 40 days after full bloom. Harvesting of safflower seed's quality is best between 20 days and 30 days after full bloom.